ChemInform Abstract: The Enantioselective Dakin—West Reaction. Issue 26 (June 2016) - Wende, Raffael C.; Seitz, Alexander; Niedek, Dominik; Schuler, Soeren M. M.; Hofmann, Christine; Becker, Jonathan; Schreiner, Peter R.
Abstract: Using an adamantane‐anchored methylimidazole‐containing oligopeptide as catalyst, the first examples for an enantioselective Dakin—West reaction are reported.